A Musician's Notes: Improvising During a Pandemic - Knowles, Liz (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
What does the music world three months into a pandemic look like to an Irish fiddler (Liz Knowles), a viola da gamba player (Liam Byrne), a violinist/pianist/composer (Dana Lyn), a Klezmer violinist (Lisa Gutkin), a world-jazz bassist (Juan Garcia Herreros), a venue owner (Terez Fraser), a concert presenter (Tom Rota), and a festival producer (Olga Barry)? Music is about arrivals, landings and leavings. As the pandemic arrived, the arts industry—and so many other aspects of life—"landed” or stopped, and we are now imagining what the future holds: what it will look like to “leave” this shutdown period and “arrive” into the new (and possibly changed) music industry.Musical improvisation is about engaging with and crafting these arrivals, landings, and leavings in the moment. These conversations in this podcast reveal some surprising aspects of the pre-pandemic music world—different musicians’ concepts of time, trajectory, and improvisation in music and in business—and also offer perspectives on how we see the future, both as individuals and as a community.